(untitled) (Philology, 2023)
This article outlines salient features of the primordial humans as portrayed in the Book of Genesis: their creation, their nature and the qualities with which they are endowed, their relation to God and the created universe, as well as their vocation and destiny. In our compass are not only the figures of Adam and Eve, but also that of Noah who, while echoing Adam, represents yet another type of the father of humankind. In Sections i–iv the Biblical accounts are analysed against the background of ancient Mesopotamian and Egyptian sources, while Section iv.i explores the localisation of the beginnings of the post-diluvian humanity on the Biblical map of the world. In Section v, a special attention is paid to the connections between the humans, the plants and the animals, before and after the flood. The focus of Section vi is on the representation of the primæval humans in Jewish and Christian para-Biblical literature. Section vii is dedicated to the reception of the Biblical tradition of human origins in the New Testament and its elaboration in early Patristic texts, apocryphal writings and figurative sources. Our investigation highlights the persistence of royal imagery in textual and figurative portrayals of Adam.